2008
DOI: 10.3151/jact.6.389
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and Molecular Weight of Superplasticizer Contained in Pore Solution Extracted from Hardened Cement Pastes

Abstract: There are concerns about the possible increase in the solubility of radionuclides due to the presence of superplasticizers proposed to be added to cementitious materials in a radioactive waste repository. The concentration and molecular weight of a polycarboxylate type SP in hardened cement pastes has been investigated experimentally in this work. The measurement of total organic carbon in both the pore water extracted from hardened cement pastes by compression and the curing water was performed. Organic subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
(5 reference statements)
2
4
0
Order By: Relevance
“…After this mixture was stored for 7 days under ambient conditions, the supernatant was separated by centrifugation to provide the sample solution containing the extracts of the super plasticizer. The molecular weight of organic materials in the solution was 200 to 300, which was similar to that of organics in the solution of cement pores reported previously (Suguro et al 2011;Fujita et al 2008). The solution was then bubbled with carbon dioxide to fix the pH to 8 with the precipitate of calcium carbonate removed by filtration using 0.45 μm membrane filter.…”
Section: Methodssupporting
confidence: 86%
See 1 more Smart Citation
“…After this mixture was stored for 7 days under ambient conditions, the supernatant was separated by centrifugation to provide the sample solution containing the extracts of the super plasticizer. The molecular weight of organic materials in the solution was 200 to 300, which was similar to that of organics in the solution of cement pores reported previously (Suguro et al 2011;Fujita et al 2008). The solution was then bubbled with carbon dioxide to fix the pH to 8 with the precipitate of calcium carbonate removed by filtration using 0.45 μm membrane filter.…”
Section: Methodssupporting
confidence: 86%
“…The concentration of total organic carbon (TOC) of the solution was adjusted to a designated value by dilution. In order to respond to a recent view that the molecular weight distribution of organic compounds originated from super plasticizers in the solution of cement pores tends to decrease in comparison with that of the original plasticizers (Suguro et al 2011;Fujita et al 2008), the super plasticizer solution for the in-situ experiments was prepared by the following procedure. A super plasticizer, Reobuild SF8LS from BASF, was mixed with a Portland cement to adsorb to the cement materials.…”
Section: Methodsmentioning
confidence: 99%
“…A study by Fujita et al (2008) concluded that more than 90% of the polycarboxylate SP remains in the cement and that only molecules of lower molecular weight, either residual monomers or degradation products, are leached into the curing water. In order to test this hypothesis and to assess the mobility of both the SP polymers and their monomers, experiments were repeated using 14 C-labelled BSP1, 14 C-labelled PEGMA and 14 C-methacrylate (MAA).…”
Section: Radionuclide Incorporationmentioning
confidence: 99%
“…These authors attributed the observed increase of solubility to the formation of mixed complexes of the radionuclides with the SP additives stabilised by hydroxyl ions. It has been pointed out that this enhancement may not be realistic since at least 90% of the SP added to the mix is likely to be retained by the cement matrix (Fujita et al, 2008;Kitamura et al, 2013). Moreover, the composition of any organic compound leached from the cement may differ from the bulk SP, as only low-molecular-weight substances, either unreacted monomer or degradation products, could be detected in the pore water (Fujita et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation